A democratização da educação no município de Sarandi, Paraná: as diretrizes educacionais do governo do PT (2001-2008) - Araújo, José Luiz [UNESP] (2014)
The struggle for the democratization of the educational management coincided with the fight of society for the redemocratization of the country, the end of 1970s. Consequently, with the end of the military regime, the principle of the democratic management of the public teaching was inscribed in the Federal Constitution of 1988, and later, in the LDBEN Law 9.493/96. Since then, the system of democratization in the educational management was inscribed in the pedagogic projects of the public educational institutions, and also in the election platforms of the political parties, including the PT (Workers‟ Party). This study analyzed the experience of the democratic management, in the city of Sarandi-PR. The research was developed in the period from 2001 to 2008, with the intention of verifying whether the elections of directors and school boards were constituted, at that moment, as political participation spaces, as well as spaces of the democratization of power relations. As specific objectives, we have situatinge the struggle of educators in favor of the democratization of the educational management, during the military regime (1964-1985); understanding the concept of education and the educational guidelines proposed by the Workers‟ Party; understanding the historical, social and political determinants that contributed to the achievement of the educational policy of the Workers‟ Party, in Sarandi; to analyzinge the educational policy developed in Sarandi, in the period from 2001 to 2008, and analyzinge the process of democratization of the educational management. The analysis materials were the educational management reports, the texts produced by the school communities, and the official documents of the municipality, produced in the period which deal with the democratization of the school management. The survey also included the application of a questionnaire for faculty and staff members who participated in the democratization...